Respuesta :
Answer:
[tex]x=-52[/tex]
Step-by-step explanation:
multiple everything by 3 to get rid of the fractions
[tex]3(1/3x-2/3=-18)\\1x-2=-54\\[/tex]
rewrite
[tex]x-2=-54[/tex]
add 2 to both sides
[tex]x-2+2=-54+2\\x=-52[/tex]
Answer:
[tex]x=-52[/tex]
Step-by-step explanation:
[tex]\frac{1}{3} x-\frac{2}{3} =-18[/tex]
Add [tex]\frac{2}{3}[/tex] to both sides of the equation:
[tex]\frac{1}{3} x=-18 +\frac{2}{3}[/tex]
Simplify [tex]-18+\frac{2}{3}[/tex] by multiplying [tex]-18[/tex] in fraction form [tex]-\frac{18}{1}[/tex] to get a common denominator so you can add the two fractions:
[tex]-\frac{18}{1}[/tex] × [tex]\frac{3}{3}=-\frac{54}{3}[/tex]
Now add the two fractions:
[tex]-\frac{54}{3} +\frac{2}{3} =-\frac{52}{3}[/tex]
Now write the simplified equation:
[tex]\frac{1}{3} x=-\frac{52}{3}[/tex]
Divide both sides of the equation by the coefficient of [tex]x[/tex], which is [tex]\frac{1}{3}[/tex]:
[tex]x=-\frac{52}{3}[/tex] ÷ [tex]\frac{1}{3}[/tex]
Use the reciprocal of the dividend ([tex]\frac{1}{3}[/tex]), and multiply by your divisor:
[tex]x=-\frac{52}{3}[/tex] × [tex]\frac{3}{1}[/tex]
[tex]x=-\frac{156}{3}[/tex]
Simplify the fraction by dividing [tex]-156[/tex] into [tex]3[/tex]:
[tex]x=-52[/tex]